Kelussia odoratissima Mozaff. activates intrinsic pathway of apoptosis in breast cancer cells associated with S phase cell cycle arrest via involvement of p21/p27 in vitro and in vivo - Karimian, H.; Arya, Aditya; Fadaeinasab, M.; Razavi, M.; Hajrezaei, M.; Khan, A.K.; Ali, Hapipah Mohd; Abdulla, Mahmood Ameen; Noordin, M.I. (Dove Medical Press, 2017)
Background: The aim of this study was to evaluate the anticancer potential of Kelussia odoratissima. Several in vitro and in vivo biological assays were applied to explore the direct effect of an extract and bioactive compound of this plant against breast cancer cells and its possible mechanism of action. Materials and methods: K. odoratissima methanol extract (KME) was prepared, and MTT assay was used to evaluate the cytotoxicity. To identify the cytotoxic compound, a bioassay-guided investigation was performed on methanol extract. 8-Hydroxy-ar-turmerone was isolated as a bioactive compound. In vivo study was performed in the breast cancer rat model. LA7 cell line was used to induce the breast tumor. Histopathological and expression changes of PCNA, Bcl-2, Bax, p27 and p21 and caspase-3 were examined. The induction of apoptosis was tested using Annexin V-fluorescein isothiocyanate (FITC) assay. To confirm the intrinsic pathway of apoptosis, caspase-7 and caspase-9 assays were utilized. In addition, cell cycle arrest was evaluated. Results: Our results demonstrated that K. odoratissima has an obvious effect on the arrest of proliferation of cancer cells. It induced apoptosis, transduced the cell death signals, decreased the threshold of mitochondrial membrane potential (MMP), upregulated Bax and downregulated Bcl-2. Conclusion: This study demonstrated that K. odoratissima exhibits antitumor activity against breast cancer cells via cell death and cell cycle arrest.